Longitudinal analysis of respiratory outcomes among bauxite exposed workers in western Australia. Issue 8 (15th June 2015) - Dennekamp, Martine; de Klerk, Nicholas Hubert; Reid, Alison; Abramson, Michael John; Cui, Jisheng; Del Monaco, Anthony; Fritschi, Lin; Benke, Geza Paul; Sim, Malcolm Ross; Musk, Arthur William; Welch, Laura; Baker, Robin
<x xml:space="preserve">Abstract</x> Introduction Occupational exposure to bauxite is common in the aluminium industry but little is known about the associated health effects. This study investigates respiratory health in relation to respirable bauxite dust exposure longitudinally over a 13 year period. Methods An inception cohort study recruited 91 male bauxite miners and 363 male alumina refinery workers. Annual measurements of respiratory symptoms and lung function were made. Cumulative exposure to bauxite was derived from job histories and air monitoring data. Mixed‐effects modeling was used. Results No associations were found between cumulative bauxite exposure and respiratory symptoms or lung function. However, when analysis was restricted to the first three rounds, FEV1 was significantly lower in all exposure groups than in those unexposed but with no significant trend. Conclusion Increasing exposure to bauxite dust in the aluminum industry was not associated with respiratory symptoms or consistent decrements in lung function. Am. J. Ind. Med. 58:897–904, 2015. © 2015 Wiley Periodicals, Inc.